PENDIDIKAN ISLAM DALAM PEMIKIRAN SYEIKH AHMAD SURKATI - Dian Permana; Mr. Supean Chemo, Lc., M.Pd. (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
Islamic education is one aspect of Islamic teachings as a whole. Therefore, the purpose of Islamic education is inseparable from the purpose of human life in Islam, namely to create personal servants of Allah who are always devoted to Him and can achieve a happy life in this world and the hereafter, and Ahmad Surkati said that humans are creatures that are perfect in order to carry out the task as caliph on earth. Ahmad Surkati further stated that human perfection needs to be empowered, this empowerment can be done with education. Because with education the potential possessed by humans can be maximized. Ahmad Surkati believes that education and teaching are the key to achieving and creating the progress of human civilization.